A review on environmental assessment of conversion of agriculture waste to bio-energy via different thermochemical routes: Current and future trends - Alhazmi, H. (Elsevier Ltd, 2021)
The investigation of the environmental impacts of different biomass valorization processes has become a âhot topicâ among the academic and industrial practitioners; starting since bio-energy is opted as a clean renewable energy to mitigate the anthropogenic greenhouse gas (GHG) emissions. Life cycle assessment (LCA) is a universal friendly tool to evaluate the impact of the energy used, release of toxic substances, natural resources involved in all life cycle stages of a product or process. Herein, in this review, we are focussing on the environmental impacts of different biomass valorization-based thermochemical conversion technologies (e.g. torrefaction, pyrolysis, gasification and liquefaction). Apart from environmental impacts, the physiochemical characteristic of different agriculture waste from various regions is also being reported to provide a full overview of thermochemical conversion of agriculture waste to bio-energy. Lastly, the research gaps and future outlook in biomass thermochemical conversion are also being discussed to enlighten the future engineer and scientist on the key takeaways in this niche area. Â© 2021 Elsevier Ltd